Persepsi Penggunaan ChatGPT sebagai Alat Bantu Belajar Mata Kuliah Pemrograman di Institut Widya Pratama - Lisatri Makna; Victorianus Aries Siswanto; Ichwan Kurniawan (Jurnal Teknologi Terpadu, 2026)
The development of artificial intelligence technology, particularly ChatGPT, has created new opportunities to support programming learning in higher education. However, studies examining students’ perceptions of ChatGPT as a support tool in programming courses remain limited, especially regarding ease of use, usefulness in completing assignments, dependency levels, and learning effectiveness. This condition indicates the need for a focused study to understand the role of ChatGPT in student learning contexts. Therefore, this study aims to analyze students’ perceptions of ChatGPT in programming learning at Institut Widya Pratama Pekalongan. This study employed a quantitative survey approach. Data were collected through questionnaires distributed to 91 students selected through purposive sampling and analyzed using validity and reliability tests and descriptive statistics. The results show that ChatGPT's ease of use received an average score of 81.31%, indicating strong agreement. The usefulness of ChatGPT in assisting with programming assignments reached 78.63%, categorized as agree. Student dependency on ChatGPT was 54.79%, categorized as neutral. Meanwhile, the effectiveness of ChatGPT usage reached 77.30%, categorized as agree. Overall, these results indicate that ChatGPT has potential as an effective support tool when used wisely.